Fabrication and Characterization Dye-Sensitized Solar Cell based on TiO2/SnO2 Composit Electrode and Polymer Electrolite - Irmansyah Irmansyah; Akhiruddin Maddu; Mahfuddin Zuhri (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
A solid-state dye-sensitized solar cell based on TiO2/SnO2 composite electrode and polyethylene glycol (PEG) based electrolyte has been fabricated. The solar cell was formed in sandwich structure, which two electrodes sandwiching polymer electrolyte containing a redox couple (I-/I3-). One of the electrode was TiO2/SnO2 composite layer on TCO (transparent conducting oxide) coated glass substrate which sensitized with Ruthenium complex dye as electron donor, and the other electrode was a carbon sheet as a counter electrode. Active area of solar cell was 1.5 cm x 1 cmm. The solar cell was tested by irradiation with mercury lamp of 400 Watt with intensity of 30 mW/cm2 at a distance of 30 cm and sunlight with intensity of 36 mW/cm2. The cell tested with mercury lamp result in an open circuit voltage (VOC) of 420 mV, short circuit current (ISC) of 52 μA, maximum power (Pmax) of 10.4 μW, fill factor (FF) of 48% and energy conversion (η) of 0.023 %. On the other hand, the cell tested with sunlight source result in VOC=480 mV, ISC=48μA, Pmax=12.6 μW, FF=55% and η=0.023%.